(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
For several thousand years, sorghum seeds have been a valuable staple food in warm climatic zones. One of the varieties of sorghum is "Dzhugara" (white dzhugara), is being used in the diet of the population of Uzbekistan, especially in the Aral Sea zones, due to drought and salt tolerance, this product is the main type of grain in the diet of the indigenous population. In the scientific literature there are numerous studies devoted to the use of sorghum only as a fodder crop, and there are no studies devoted to the use of this product in dietetics and the study of the biological value of local varieties in Uzbekistan. The author conducted studies to study the amino acid composition of sorghum grain of the "Dzhugara" variety and showed its preventive and dietary properties due to the high content of essential amino acids methionine in the amount of 9.051139 ± 0.0234 mg / gm and leucine in the amount of 6.8521±0.0245 mg/ gm, the so-called lipotropic substances, which are necessary especially for diabetes mellitus, chronic liver disease, obesity and metabolic syndrome.